Organizational Culture at Starbucks - Sin Yan Goh; Daisy Mui Hung Kee; Qing Er Ooi; Jia Jie Boo; Pei Ying Chen; Asla Alosaimi; Megha Ghansal (AIBPM Publisher, 2020)
The importance of organizational culture has always been the subject of organizational success. Organizational culture has captured the attention of academic scholars. Organizational culture plays an important role for an organization to build its branding. Organizational culture can be used as a powerful engine of competitive advantage and thus allow an organization to integrate its culture and branding to produce phenomenal results. A good organizational culture will result in a strong brand. The paper presents the organizational culture in Starbucks, an American coffee company. As a brand of 48 years, Starbucks has successfully instilled their cultures especially their shared values to employees. This move enables Starbucks to be one of the most successful brands in the century. This paper also investigates the reasons behind its success as well as the relationship between them.